DM1: autoetnografía de un cuerpo en disputa - Arce Coronel, Xiomi Camila (2025)
This chronic explores the experience of living with a chronic disease, type 1 diabetes mellitus (DM1), from an autoethnographic perspective, highlighting the tensions between Western biomedicine and traditional and alternative therapies in a hybrid cultural context. Through a narrative that encompasses diagnosis, treatment, and cultural implications, it reflects on how the disease becomes a frontier between different systems of knowledge and power. In addition, the impact of these experiences on identity, the body, and conceptions of health are analyzed, addressing illness not only as a physiological phenomenon, but also as a cultural, symbolic, and political phenomenon. In this process, writing becomes a tool to understand and resignify vulnerability and the relationship with the body.